Supraclavicular Block for ORIF of Distal Humerus Fracture in End-Stage Renal Disease: A Case Report - Dessy Kusumadewi; Taufiq Siswagama (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2026)
Supraclavicular block (SCB) is a well-established regional anesthesia technique for upper limb surgery; however, its application in patients with end-stage renal disease (ESRD) receiving antiplatelet therapy presents distinct clinical challenges. This case is noteworthy because of the coexistence of ESRD, ongoing clopidogrel therapy, anemia, and potential respiratory compromise, all of which complicate anesthetic decision-making. We report a 44-year-old female with ESRD on regular hemodialysis who sustained a comminuted intra-articular distal humerus fracture and underwent open reduction and internal fixation under ultrasound-guided SCB. The block was performed using 15 mL of 0.75% ropivacaine with dexamethasone as an adjuvant, following careful consideration of bleeding risk, local anesthetic dosing, and pneumothorax prevention. The procedure provided effective intraoperative anesthesia and prolonged postoperative analgesia without neurological, respiratory, or bleeding complications. Postoperative pain scores remained low, opioid consumption was minimal, and motor function recovered uneventfully. This case highlights that ultrasound-guided SCB can be safely and effectively performed in carefully selected ESRD patients receiving antiplatelet therapy when meticulous technique, dose justification, and risk mitigation strategies are applied. The key learning point is the importance of individualized anesthetic planning rather than a generalized preference for regional over general anesthesia.